Bioaugmentation with Immobilized Microorganisms to Enhance Phytoremediation of PCB-Contaminated Soil. Issue 4 (18th May 2016) - Pino, Nancy J.; Muñera, Luisa M.; Peñuela, Gustavo A.
ABSTRACT: The aim of this study was evaluate the effect of bioaugmentation by free and immobilized strains of microbial consortium on the phytoremediation of polychlorinated biphenyl (PCB)-contaminated soil using the Avena sativa, Brachiaria decumbens, Brassica juncea, and Medicago sativa plants. Alginate and biochar were used as carrier materials and free cells were used as the control. PCBs 44, 66, 118, 138, 153, 170, and 180 were chosen as indicator PCB congeners. After 60 days of plant growth, the concentration of each congener and the survival of the microbial inoculum were evaluated. The removal of the PCB congener was greater in B. juncea planted treatments and using biochar as a carrier material. PCB 66 was the congener with the highest removal percentage in all using biochar and alginate-immobilized microorganisms and free microorganisms, while PCB 170 had the lowest removal percentage in all treatments. The largest removal percentage for all congeners was obtained using biochar as a carrier material (7.2–30.3%) and the lowest with planted treatments using free microorganisms (2.3–6.8%). Real-time polymerase chain reaction (PCR) showed that the microbial inoculum survived when it was immobilized using both alginate and biochar without any significant differences between treatments; however, PCB removal percentages were obtained with biochar, which demonstrated that this carrier material has a positive effect on microbial activity.